Use of Antibiotics for acute respiratory infection (ARI) in Puskesmas Karang Rejo, Tarakan - Mirza Insani; Dharma Permana (Yarsi Journal of Pharmacology, 2020)
Background: Acute respiratory infection (ARI) is a serious infection that prevents normal breathing function. It usually begins as a viral infection in the nose, trachea (windpipe), or lungs. If the infection is not treated, it can spread to the entire respiratory system. ARI prevents the body from getting oxygen and can result in death. ARI is the most common diagnosis for which antibiotics are prescribed and there are many reasons why primary care doctors prescribe antibiotics. The aim of this study was to know the use of antibiotic drugs in ARI patients at Puskesmas Karang Rejo, Tarakan.Methods: The research method is a descriptive with retrospective data collection by collecting secondary data obtained from medical records at Puskesmas Karang RejoTarakan in the period of January-April 2017. Results: A total of 595 medical records were selected, there were 58.66% (n = 349) female and 41.34 % (n = 246) male, and most occurred in children aged 1-5 years 31.60% (n=188) and aged 6 -10 years 20.84% (n=124). The most common types of ARI were acute tonsillitis 33.61% (n=200), nonspecific respiratory tract infection 32.77% (n=195) and pneumonia 13,94% (n=83. The antibiotic drugs used were amoxicillin 73.11% (n=435), cotrimoxazole 22.02% (n=131), ciprofloxacin 2.52% (n=15), cephadroxil 1.68% (n=10) and chloramphenicol  0.67% (n=4). Amoxicillin and cotrimoxazole were the most commonly used antibiotic for treatment of patients with all types of ARI. Amoxicillin use was highest in acute tonsillitis (94.00%, n=188) and nonspecific respiratory tract infection (85.13%, n=166), while cotrimoxazole use was highest in pneumonia (90.36%, n=75).Conclusion: Amoxicillin and cotrimoxazole were the mostly used antibiotics for treatment of patients with ARI in Puskesmas Karang Rejo, Tarakan.